Faktor-Faktor yang Mempengaruhi Pembuangan Sampah Pasar Tradisional Darfuar Kabupaten Biak Numfor Tahun 2020 - Anna Dwiana (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
The waste problem has become a serious problem, especially in big cities, not only in Indonesia, but throughout the world. Waste production that continues to increase along with population growth, changes in consumption patterns, people's lifestyles has increased the amount of waste piles, types and diversity of waste characteristics. This study aims to determine the factors that influence the disposal of waste from the Darfuar traditional market in Biak Numfor Regency. This type of research is a quantitative analytic which tries to explore and why health phenomena occur, with a cross sectional design. The population in this study were 234 respondents. The sample in this study were 147 respondents, where the sampling was random sampling. The results of the chi-square statistical test obtained the value of X2 count = 4.506 (X2 table = 3.841), the value of ? = 0.039. Thus the calculated X2 is greater than the X2 table or ? = 0.039 is smaller than ? = 0, the X2 count = 6.835 (X2 table = 3.841), the value ? = 0.015. Thus X2 count is greater than X2 table or ? = 0.015 is smaller than ? = 0.05, the value of X2count = 9.093 (X2 table = 3.841), the value of ? = 0.004. Thus X2 count is greater than X2 table or ? = 0.004 smaller than ? = 0.05, so Ho is rejected and Ha is accepted, meaning that there is an influence between waste facilities on Darfuar Market Waste Disposal in Biak Numfor Regency in 2020.